2015
DOI: 10.1681/asn.2014080834
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Hypertension in Transplant Patients

Abstract: Hypertension in renal transplant recipients is common and ranges from 50% to 80% in adult recipients and from 47% to 82% in pediatric recipients. Cardiovascular morbidity and mortality and shortened allograft survival are important consequences of inadequate control of hypertension. In this review, we examine the epidemiology, pathophysiology, and management considerations of post-transplant hypertension. Donor and recipient factors, acute and chronic allograft injury, and immunosuppressive medications may eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 115 publications
(96 reference statements)
2
112
2
12
Order By: Relevance
“…The use of CCB is also associated with earlier allograft function recovery. Whether this results in long-term graft protection is however, unclear [1]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CCB is also associated with earlier allograft function recovery. Whether this results in long-term graft protection is however, unclear [1]. …”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence, defined as the use of antihypertensive agents with or without elevated blood pressure (BP), has been reported to be as high as 85% [1]. It is generally accepted that hypertension negatively influences kidney transplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation, however, was not graded due to the lack of evidence supporting this statement. 75 A recent review by Weir et al 76 They showed that use of these agents was associated with a significant reduction in proteinuria and GFR, but there was insufficient data to draw any conclusions regarding graft or patient survival.…”
Section: Blockade Of the Rennin-angiotensin Systemmentioning
confidence: 99%
“…76,95 A recent search of clinicaltrials. gov identified 2 proteinuria trials in renal transplantation.…”
Section: Future Directionsmentioning
confidence: 99%
“…BP threshold for treatment of kidney transplant recipients remains at 130/80 mm Hg, regardless of proteinuria. 9 The Secondary Prevention of Small Subcortical Strokes (SPS3) trial, which compared an SBP treatment target of <130 mm Hg with a target of 130 mm Hg to 149 mm Hg in participants with a recent lacunar stroke, showed a nonsignificant reduction in recurrent stroke in the group randomized to the lower target. 10 There are no specific studies that have evaluated BP targets in patients without other comorbidities who are younger than 50 years and who often have predominantly diastolic hypertension.…”
mentioning
confidence: 99%